Efektivitas Pembelajaran Matematika Melalui Penerapan Pendekatan Kontekstual Pada Siswa Sekolah Menengah Pertama - Ahmad Farham Majid (Alauddin Journal of Mathematics Education, 2022)
The lack of understanding of students on other given problems indicates that students do not have conceptual abilities. This study aims to determine the effectiveness of mathematics learning through the application of a contextual approach to grade VIII students of SMP Nasional Makassar. The sample used is Cluster Random Sampling, where one class is randomly selected from six classes to determine the experimental class and the selected one is class VIIIF. In conducting research, mathematics learning outcomes tests are used, student activity observation sheets, learning implementation observation sheets, and student response questionnaires. Data collected through learning outcomes tests, student activity sheets, learning implementation sheets and questionnaires of student responses to mathematics learning through the application of a contextual approach will be analyzed using descriptive statistical analysis techniques. The results of the analysis showed the completeness of mathematics learning outcomes with a score of 87.50%, student activities in participating in learning for four meetings were in the effective category, the percentage of learning implementation through the application of a contextual approach was 89.58%, based on the analysis of student response questionnaires obtained the average percentage of students who gave positive responses was 86.79%.